Synergistic effect of binary ligands on nucleation and growth/size effect of nanocrystals: Studies on reusability of the solvent. Issue 14 (4th August 2014) - H.R., Chandan; V., Saravanan; Krishna Pai, Ranjith; Geetha Balakrishna, R.
Abstract: Abstract : An attempt to reduce the effect of major toxic components namely phosphine ligands and unsaturated solvents as being used in conventional nanocrystal synthesis, has been made with a new binary ligand, and a reusable solvent N-octadecane for a smokeless and clean synthesis procedure. The optimized effects of the two ligands oleic acid and octadecyl amine on the nucleation rate and growth of CdSe nanocrystals (NCs) are reported and substantiated by AFM analysis. Oleic acid accelerates particle ripening and nuclei growth, but inhibits nucleation whereas octadecyl amine catalyses nucleation and very gradually improves growth to obtain small stable NCs. Another important feature of the present study is the replacement of 1-octadecene by a competitive N-octadecane as a solvent in such ligand mediated nanocrystal synthesis. The GCMS analysis reports a recovery of 95% of solvent after reuse, thus opening a scope for environmental friendly processes.